Targeted Chemotherapy: Platinum on Nanodiamond: A Promising Prodrug Conjugated with Stealth Polyglycerol, Targeting Peptide and Acid‐Responsive Antitumor Drug (Adv. Funct. Mater. 34/2014). (September 2014) - Zhao, Li; Xu, Yong‐Hong; Qin, Hongmei; Abe, Shigeaki; Akasaka, Tsukasa; Chano, Tokuhiro; Watari, Fumio; Kimura, Takahide; Komatsu, Naoki; Chen, Xiao
<x xml:space="preserve">Abstract</x> On page 5348, N. Komatsu, X. Chen, and colleagues demonstrate multifunctional anticancer prodrug consisting of nanodiamond core, polyglycerol coating, targeting peptide and platinum‐based drugs. The resulting good aqueous solubility, stealth nature, and targeting property enable the nanodiamond‐based prodrug to be taken up selectively by cancer cells overexpressing αvβ3 integrin and to cause the selective cell death through acid‐responsive drug release. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>